High gene flow in polar cod (Boreogadus saida) from West‐Svalbard and the Eurasian Basin. Issue 1 (1st March 2021) - Maes, Sarah M.; Christiansen, Henrik; Mark, Felix C.; Lucassen, Magnus; Van de Putte, Anton; Volckaert, Filip A.M.; Flores, Hauke
Abstract: The current and projected environmental change of the Arctic Ocean contrasts sharply with the limited knowledge of its genetic biodiversity. Polar cod Boreogadus saida (Lepechin, 1774) is an abundant circumpolar marine fish and ecological key species. The central role of polar cod in the Arctic marine food web warrants a better understanding of its population structure and connectivity. In this study, the genetic population structure of 171 juveniles, collected from several fjords off West‐Svalbard (Billefjorden, Hornsund and Kongsfjorden), the northern Sophia Basin and the Eurasian Basin of the Arctic Ocean, was analysed using nine DNA microsatellite loci. Genetic analyses indicated moderate to high genetic diversity, but absence of spatial population structure and isolation‐by‐distance, suggesting ongoing gene flow between the studied sampling regions. High levels of connectivity may be key for polar cod to maintain populations across wide spatial scales. The adaptive capacity of the species will be increasingly important to face challenges such as habitat fragmentation, ocean warming and changes in prey composition. In view of a limited understanding of the population dynamics and evolution of polar cod, a valuable next step to predict future developments should be an integrated biological evaluation, including population genomics, a life‐history approach, and habitat and biophysical dispersal modelling.